Mixed methods evaluation of the impact of the COVID-19 ICU remote-learning rehabilitation course for frontline health professionals during the COVID-19 pandemic in the UK. (November 2022) - Corner, Evelyn J; Zhang, Xiaoxi; Van Willigen, Zoe; Tatam, Kate; Camilleri, Matthew; Monkhouse, Alex; Bear, Danielle E; Hemsley, Alex; Puthucheary, Zudin; Rosenberg, Alex; McRae, Jackie; Harvey, Alex; et al.
Background: Optimising outcomes for critically ill patients with COVID-19 patients requires early interdisciplinary rehabilitation. As admission numbers soared through the pandemic, the redeployed workforce needed rapid, effective training to deliver these rehabilitation interventions. Methods: The COVID-19 ICU Remote-Learning Rehab Course (CIRLC-rehab) is a one-day interdisciplinary course developed after the success of CIRLC-acute. The aim of CIRLC-rehab was to rapidly train healthcare professionals to deliver physical, nutritional and psychological rehabilitation strategies in the ICU/acute setting. The course used blended learning with interactive tutorials delivered by shielding critical care professionals. CIRLC-rehab was evaluated through a mixed-methods approach, including questionnaires, and follow-up semi-structured interviews to evaluate perceived impact on clinical practice. Quantitative data are reported as n (%) and means (SD). Inductive descriptive thematic analysis with methodological triangulation was used to analyse the qualitative data from the questionnaires and interviews. Results: 805 candidates completed CIRLC-rehab. 627 (78.8%) completed the post-course questionnaire. 95% ( n = 596) found CIRLC-rehab extremely or very useful and 96.0% ( n = 602) said they were very likely to recommend the course to colleagues. Overall confidence rose from 2.78/5 to 4.14/5. The course promoted holistic and humanised care, facilitated informal networks, promoted interdisciplinary working and equipped the candidates with practical rehabilitation strategies that they implemented into clinical practice. Conclusion: This pragmatic solution to educating redeployed staff during a pandemic increased candidates' confidence in the rehabilitation of critically ill patients. There was also evidence of modifications to clinical care utilising learning from the course that subjectively facilitated holistic and humanised rehabilitation, combined with the importance of recognising the humanity, of those working in ICU settings themselves. Whilst these data are self-reported, we believe that this work demonstrates the real-term benefits of remote, scalable and rapid educational delivery.